High-Temperature Properties of LP-DED Additive Manufactured Ferritic STS 430 Deposits on Martensitic STS 410 Base Metal - Samsub Byun; Hyun-Ki Kang; Namhyun Kang; Seunghun Lee (Micromachines)
The aim of this work is to study the phase transformations, microstructures, and mechanical properties of ferritic stainless steel (FSS) 430 deposits on martensitic stainless steel (MSS) 410 base metal (BM) using laser powder-directed energy deposition (LP-DED) additive manufacturing. The LP-DED additive manufactured FSS 430 deposits on MSS 410 BM underwent post-heat treatment at 815 °C and 980 °C for 1 h, respectively. The analyses of phase transformations and microstructural evolutions of LP-DED FSS 430 on MSS 410 BM were carried out using X-ray diffraction, SEM, and EBSD. The highest strain was observed at the coarsened chromium carbide (Cr23C6) in the joint interface between AM FSS 430 and MSS 410 MB. This contributed to localized lattice distortion and mismatch in crystal structure between chromium carbide and the surrounding ferrite. Tensile strength properties at elevated temperatures were discussed to investigate the effects of the different post-heat treatments. The tensile properties of the as-built samples including tensile strength of about 550 MPa and elongation of about 20%, were the same as those of the commercial FSS 430 material. Tensile properties at 500 °C indicated a modest increase in tensile strength to 540–550 MPa. The specimens heat treated at 980 °C retained higher tensile strength than those heat treated at 815 °C. This would be attributed to the grain refinement from prior LP-DED microstructure and chromium carbide coarsening at higher heat treatment, which can increase dislocation density and yield harder mechanical behavior.